The Correlation of Family and Household Factors on The Incidence of Stunting on Toddlers in Three Villages Sumberbaru Health Center Work Area of Jember - Farmarida Dika Rufaida; Angga Mardro Raharjo; Adelia Handoko (Journal of Agromedicine and Medical Sciences, 2020)
Stunting is a condition of the child's length or height according to his age compared to the WHO standard, the z-score is less than -2SD. Stunting is caused by multifactorial which can affect directly or indirectly and causes various adverse effects. The purpose of this study was to determine the correlation of family and household factors on the incidence of stunting (especially sex of toddler, age of toddler, father's education, mother's education, mother's employment status, number of children, birth distance, family income, and mother's height) in three villages Sumberbaru Health Center Work Area of Jember. This type of research is observational analytic research with cross-sectional research design. A sample of 130 people who met the inclusion and exclusion criteria. The sampling technique uses purposive sampling technique. Bivariate analysis using chi-square test and multivariate analysis using binary logistic regression. The results of the bivariate analysis of this study showed p <0.05 on sex of toddler, number of children, family income, mother’s height, and p > 0.05 on age of toddler, father's education, mother's education, mother's employment status, birth distance. Multivariate analysis showed mother's height <147cm (p = 0,007; OR = 3,345), family income below UMK Jember (p = 0,045; OR = 2,344), and male sex (p = 0,044; OR = 0,456 ). Based on these results it can be concluded that the incidence of stunting is directly affected by mother's height <147cm, family income below UMK Jember, and male sex of boys. While indirectly affected by the number of children >2. Factors that did not affect the incidence of stunting were the age of the toddler, father's education, mother's education, mother's employment status, and birth distance. Mother's height <147cm is the most influencing factor.